Greener Method for the Application of TiO2 Nanoparticles to Remove Herbicide in Water - Hoang Hiep; Pham Tuan Anh; Van-Duong Dao; Dang Viet Quang (Journal of Analytical Methods in Chemistry, 2023)
TiO2 nanoparticles have emerged as a great photocatalyst to degrade organic contaminants in water; however, the nanoparticles dispersed in water could be difficult to be recovered and potentially become contaminant. Herbicide like 2,4-dichlorophenoxyacetic acid (2,4-D) used in agriculture usually ends up with a large fraction remaining in water and sediment, which may cause potential risk to human health and the ecosystem. This study proposes a greener method to utilize TiO2 as photocatalyst to remove 2,4-D from water. Accordingly, TiO2 nanoparticles (10–45 nm) were synthesized and grafted on lightweight fired clay to generate a TiO2-based floating photocatalyst. Experimental testing revealed that 60.2% of 2,4-D (0.1 mM) can be decomposed in 250 min under UV light with TiO2-grafted lightweight fired clay floating on water. Degradation fits well into the pseudo-first-order kinetic model. The floating photocatalysts can degrade approximately 50% 2,4-D in 250 min under sunlight and the degradation efficiency is stable for cycles. The results revealed that the fabrication of floating photocatalyst could be a promising and greener way to remove herbicide contaminants in water using TiO2.